Ptolemaic Scotland: Some new suggestions based on recent research and on the work of Glazenbrook Rylands - Richmond, Ian A (Proceedings of the Society of Antiquaries of Scotland, 1922)
A revision of the Ptolemaic geography of Scotland based on new archaeological discoveries. In Ptolemy's map there is an eastern coast-line which for all its faults is unmistakably clear from the Tweed as far as the Moray Firth. Also it may be noted that among the land-stations, although for the most part their positions seem unlike anything that we know of the topography of Roman Scotland, there would appear to be a very definite scheme of plotting out.